Agents of disorder : inside China's Cultural Revolution - Walder, Andrew G. (Andrew George), 1953- (The Belknap Press of Harvard University Press, 2019)
Agents of Disorder is the first book to shed a clarifying light on the pattern of rebellion and repression that swept across China during the tumultuous first years of China's Cultural Revolution. Among its novel discoveries is the crucial role played by supposed "forces of order" in the collapse of the state and the subsequent intensification of collective violence. Internal rebellions by party-state cadres were crucial in the collapse of the state in early 1967, and the intervention of army units nationwide, instead of stabilizing the situation, accelerated the slide into factional warfare. Also notable is the finding that the vast majority of the estimated 1.6 million who died during these upheavals, and the close to 25 million estimated to have directly suffered political persecution, were victims not of the violent upheavals, but of the repression that re-established political order.--